RADIATION OF A SLOT IN HIGH-SPEED DIGITAL SYSTEMS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
The miniaturization of the digital electronic systems, the increase of the frequency, and the decrease of the power level make the electromagnetic compatibility issues a very important domain in the designing process of digital electronics. Both, printed circuit boards (PCBs) and the enclosure of the digital systems contain slots of different dimensions for connectors and for expansion cards. If they are excited by currents (for example by common currents), or by field distributions, they will radiate electromagnetic energy in the surroundings producing electromagnetic interferences. The paper is studying the electromagnetic field radiated by a slot cut in a conductive surface in the frequency range of 1 to 40 GHz
Keywords: Radiation; Slot; Electromagnetic compatibility; High-speed digital systems